Detroit workers news special, 1932 Ford massacre - Film and Photo League (U.S.); Museum of Modern Art (New York, N.Y.). Circulating Film Library (New York : Museum of Modern Art Film Library, 1982)
Shows the march to Grand Circus Park through bitter cold and snow to petition for unemployment relief and oppose President Hoover and Mayor Murphys̓ "starvation program."
Editors, Joseph P. Hudyma, Lester Balog.
Keywords: Depressions -- 1929 -- United States; Detroit (Mich.) -- Demonstration, 1932.